2005
DOI: 10.1063/1.2012513
|View full text |Cite
|
Sign up to set email alerts
|

The importance of network structure in high-k dielectrics: LaAlO3, Pr2O3, and Ta2O5

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Hence, the material structure, whether amorphous or arranged in different crystalline geometries, may have a considerable influence [5]. Moreover, for higher k-values, when a/V m approaches the asymptote, a small change in crystalline structure may give rise to a large change in dielectric constant [6]. In this regime, therefore, the material may be expected to show a higher sensitivity to structural perturbation or even, as for ferroelectric materials, pass through a ''polarization catastrophe'' [3].…”
Section: Physical Properties Of Dielectricsmentioning
confidence: 98%
“…Hence, the material structure, whether amorphous or arranged in different crystalline geometries, may have a considerable influence [5]. Moreover, for higher k-values, when a/V m approaches the asymptote, a small change in crystalline structure may give rise to a large change in dielectric constant [6]. In this regime, therefore, the material may be expected to show a higher sensitivity to structural perturbation or even, as for ferroelectric materials, pass through a ''polarization catastrophe'' [3].…”
Section: Physical Properties Of Dielectricsmentioning
confidence: 98%
“…Recently, complex rare earth (RE) and transition metal (TM) oxides (such as LaAlO 3 [4], Dy 0:1 Hf 0:9 O x [5], and La 2 (Zr,Hf) 2 O 7 [6,7]) attract considerable interests as candidate high-k gate dielectrics for silicon MOS devices. It has been found that alloying La-based oxide and HfO 2 have advantages as follows: (i) the crystallization temperature can be raised without lowing k; (ii) La-based oxides have a larger conduction band offset and lower leakage current.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the material structure, whether amorphous or arranged in different crystalline geometries, may have a considerable influence on the kvalue. Furthermore, when α/V m approaches the asymptote, a small change in the crystallinity of the structure may give rise to a large change in the dielectric constant [34]. …”
mentioning
confidence: 99%